Explorations in environmental history : essays - Hays, Samuel P.; Tarr, Joel A. (Joel Arthur), 1934- (Pittsburgh, Pennsylvania : University of Pittsburgh Press, 1998)
Exploration in Environmental History represents four decades of writing from one of the most distinguished scholars in the field of environmental history. Samuel Hays's dedication and research is apparent in every one of these essays, four of which are published here for the first time.
The Politics of Environmental AdministrationNotes; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Environmental policy -- United States -- History; Environmentalism -- United States -- History; Air -- Pollution -- Government policy -- United States -- History; Forest ecology -- Government policy -- United States -- History; Environnement -- Politique gouvernementale -- États-Unis -- Histoire; Écologie forestière -- Politique gouvernementale -- États-Unis -- Histoire; HISTORY -- General; Air -- Pollution -- Government policy; Environmental policy; Environmentalism; United States; Environmental Sciences; Earth & Environmental Sciences; History